ChemInform Abstract: Bis(acetylacetonato)Ni(II)/NaBHEt3‐Catalyzed Hydrosilylation of 1, 3‐Dienes, Alkenes and Alkynes. Issue 32 (22nd July 2016) - Srinivas, Venu; Nakajima, Yumiko; Ando, Wataru; Sato, Kazuhiko; Shimada, Shigeru
Abstract: Commercially available Ni(acac)2 is introduced as an efficient catalyst for hydrosilylation reactions of various types of unsaturated compounds in the presence of NaBHEt3 .